Library instruction for medical students during a curriculum elective. - Mueller, M H (1987)
The University of Minnesota Medical School has an innovative curriculum, called Didactic/Selective, which provides third- and fourth-year medical students with multidisciplinary and multispecialty courses. Within this framework, the Bio-Medical Library planned a course to teach the knowledge and skills necessary for library research and information management. It included (1) searching case-related topics in print indexes, (2) formulating and processing MEDLINE searches on BRS Colleague, (3) building a personal file with PC-File or Notebook, and (4) exploring various methods for current awareness. Students' evaluations were positive, with the majority indicating that they found the course interesting and the knowledge gained substantial.